Attributes Of Antioxidants As Inferred From The Makki And Madani Verses Of The Qur'an - Latifah Abdul Majid; Wan Nasyrudin Wan Abdullah; Aminah Abdullah; Fadlan Mohd Othman; Nurul Mukminah Zainan Nazri (IIUM Press, 2024)
Volume : 4 No:1